Influence of the digital economy on economic growth: empirical study of a region in Indonesia - Indra Suhendra; Navik Istikomah; Cep Jandi Anwar; Apip Supriadi; Ali Abdul Wakhid; Eka Purwanda; Agus Salim (Cogent Economics & Finance)
This research seeks to explore how the digital economy affects economic growth in 34 provinces in Indonesia by analyzing quarterly data from 2017 to 2022 using dynamic panel GMM estimation techniques. The findings indicated a lasting connection between the economy and economic growth along with a beneficial influence on economic development. The results suggest that policymakers should prioritize promoting the adoption of economic initiatives. Next on the agenda was the necessity of implementing regulations to govern commerce and offer perks to companies using technology. Subsequently, there was a need to improve the infrastructure of information and communication technology (ICT) and give priority to its accessibility across all regions. Furthermore, there is a call to enhance the skills and proficiency of workers and human resources within the ICT industry. Lastly, A crucial aspect is the call for investments aimed at boosting capabilities within the ICT and electronic business sectors.